Stability of anterior open bite treatment with molar intrusion using skeletal anchorage: a systematic review and meta-analysis - Daybelis González Espinosa; Paulo Eliezer de Oliveira Moreira; Amanda Silva da Sousa; Carlos Flores-Mir; David Normando (SpringerOpen, 2020)
Abstract Objectives The aim of this systematic review and meta-analysis is to assess the degree of stability of anterior open bite (AOB) treatment performed through the molar intrusion supported with skeletal anchorage at least 1 year posttreatment. Methods This study was registered in PROSPERO (CRD42016037513). A literature search was conducted to identify randomized (RCT) or non-randomized clinical trials based including those considering before and after design. Data sources were electronic databases including PubMed, Cochrane Library, Science Direct, Google Scholar, Scopus, Lilacs, OpenGrey, Web of Science, and ClinicalTrials.gov . The quality of evidence was assessed through the JBI tool and certainty of evidence was evaluated through the GRADE tool. Random effects meta-analysis was conducted when appropriate. Results Six hundred twenty-four articles met the initial inclusion criteria. From these, only 6 remained. The mean posttreatment follow-up time was 2.5 years (SD = 1.04). The overbite showed a standardized mean relapse of − 1.23 mm (95% CI − 1.64, − 0.81, p < 0.0001). Maxillary and mandibular incisors presented a non-significant mean relapse, U1-PP − 0.04 mm (95% CI − 0.55, 0.48) and L1-MP − 0.10 mm (95% CI − 0.57, 0.37). Molar intrusion showed a relapse rate around 12% for the maxillary molars and a 27.2% for mandibular molars. Conclusion The stability of AOB through molar intrusion using TADs can be considered relatively similar to that reported to surgical approaches, since 10 to 30% of relapse occurs both in maxillary and mandibular molars. The level of certainty ranged between very low and low. RCTs reporting dropout during the follow-up are in dire need.